The Myth of Total Shakespeare: Filmic Adaptation and Posthuman Collaboration - Lewis, Seth (Multicultural Shakespeare: Translation, Appropriation and Performance, 2021)
The convergence of textuality and multimedia in the twenty-first century signals a profound shift in early modern scholarship as Shakespeare’s text is no longer separable from the diffuse presence of Shakespeare on film. Such transformative abstractions of Shakespearean linearity materialize throughout the perpetual remediations of Shakespeare on screen, and the theoretical frameworks of posthumanism, I argue, afford us the lens necessary to examine the interplay between film and text. Elaborating on André Bazin’s germinal essay “The Myth of Total Cinema,” which asserts that the original goal of film was to create “a total and complete representation of reality,” this article substantiates the posthuman potentiality of film to affect both humanity and textuality, and the tangible effects of such an encompassing cinema evince themselves across a myriad of Shakespearean appropriations in the twenty-first century (20). I propose that the textual discourses surrounding Shakespeare’s life and works are reconstructed through posthuman interventions in the cinematic representation of Shakespeare and his contemporaries. Couched in both film theory and cybernetics, the surfacing of posthuman interventions in Shakespearean appropriation urges the reconsideration of what it means to engage with Shakespeare on film and television. Challenging the notion of a static, new historicist reading of Shakespeare on screen, the introduction of posthumanist theory forces us to recognize the alternative ontologies shaping Shakespearean appropriation. Thus, the filmic representation of Shakespeare, in its mimetic and portentous embodiment, emerges as a tertiary actant alongside humanity and textuality as a form of posthuman collaboration.